Detection of parasites in marine fish for human consumption in Lima - Serrano-Martínez, Enrique (2017)
The aim of this study was to evaluate the presence of parasites in five species of marine fish (Sarda chiliensis chiliensis [Eastern Pacific bonito], Scomber japonicus peruanus [Pacific chub mackerel], Trachurus picturatus murphyi [Chilean jack mackerel], Mugil cephalus [flathead grey mullet], and Coryphaena hippurus [common dolphinfish]) intended for human consumption. A total of 150 fish were used (30 per species) from the fishing terminals of Chorrillos and Villa María del Triunfo in the province of Lima, Peru, between January to March 2014. It was found 13 species of parasites: monogeneans (Monocotile sp), digenea (Dinurus sp), protozoa (Henneguya sp), acanthocephalan (Rhadinorhynchus sp), cestoda (Diphyllobothrium pacificum, Hepatoxylon trichiuri, Tentacularia coryphaenae, Nybelinia sp), nematoda (Anisakis simplex, Anisakis physeteris, Contracaecum sp, Proleptus sp) and arthropods (Caligus sp). The results showed that 61.3% of the specimens had at least one parasite, having the flathead grey mullet a higher prevalence (86.7%), followed by the common dolphinfish (76.7%). Similarly, greater parasite load was observed in flathead grey mullet (424) and Eastern Pacific bonito (376). The most common parasites were Hepatoxylon trichiuri, Nybelinia sp and Proleptus sp. Parasites of public health importance were found shuch as Anisakis sp in all species except for the flathead grey mullet and Diphyllobothrium pacificum in Eastern Pacific bonito and common dolphinfish.